Implementation of Videos to Improve the Ability of Tenth Grade Students at SMK Negeri 5 Palu in Writing Procedure Texts - Ramadani, Dinda; Usman, Sriati; Wahyudin, Wahyudin (Journal of English Language and Education, 2025)
This research investigates the use of video media to improve the ability of tenth-grade students at SMK Negeri 5 Palu in writing procedure texts. Many students still face challenges in generating ideas, organizing steps, and applying correct vocabulary and grammar. This study aims to determine the effectiveness of video-based instruction in enhancing students’ writing performance. A quasi-experimental design was applied, using pre-test and post-test assessments for both experimental and control groups. Writing ability was measured based on content, organization, vocabulary, grammar, and mechanics. The findings reveal a significant improvement in the experimental group after the treatment, with the mean score increasing from 5.06 to 11.24. A paired sample t-test showed Sig. (2-tailed) = 0.000, indicating a statistically significant difference. These results confirm that the use of video media is effective in improving students’ procedural text writing ability.